2009
DOI: 10.1002/jat.1427
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine‐induced synophthalmia in sheep: defining a critical window and toxicokinetic evaluation

Abstract: Cyclopamine, a steroidal alkaloid, from the plant Veratrum californicum is teratogenic, causing a range of different birth defects. The critical window for cyclopamine-induced synophthalmia formation has been reported to be gestational day (GD) 14. The objectives of this study were to better describe cyclopamine-induced craniofacial deformities, to better define the window of susceptibility to synophthalmia formation, and to characterize cyclopamine toxicokinetics in sheep. Ewes were dosed i.v. with purified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…It remains to be determined whether the observed changes are the result of direct or indirect effects of LPS and Beta with these developmental pathways. On the basis of these results, intervention studies using inhibitors of the Shh pathway [e.g., cyclopamine (53)] would be helpful. The developing lung is plastic in that it is continually changing over gestation.…”
Section: Lps Exposure Leads To Changes In Shh Signaling In the Fetal mentioning
confidence: 99%
“…It remains to be determined whether the observed changes are the result of direct or indirect effects of LPS and Beta with these developmental pathways. On the basis of these results, intervention studies using inhibitors of the Shh pathway [e.g., cyclopamine (53)] would be helpful. The developing lung is plastic in that it is continually changing over gestation.…”
Section: Lps Exposure Leads To Changes In Shh Signaling In the Fetal mentioning
confidence: 99%
“…2A in the article by Middleton elsewhere in this issue), is part of a wide range of craniofacial abnormalities arising from the teratogenic action of the alkaloidal steroid cyclopamine, 19,20 but with a relatively narrow window of activity, both temporally and dose-related. 21 Cyclopamine inhibits the hedgehog signal transduction pathway. Mouse embryos cultured in the presence of cyclopamine to silence their sonic hedgehog gene show these changes of cyclopia and the associated developmental brain defect holoprosencephaly.…”
Section: Cyclopiamentioning
confidence: 99%
“…Based on anamnesis at the same grazing region, there was no malformation case seen either in the herd that the case was observed or in the other closer herds. It may be mentioned that viral agents has no effect on malformation in this lamb.Many cyclopia cases occurring in high incidence (25%) have been reported in the sheep herds grazing in the field containing Veratrum californicum plant which has a teratogenic effect in sheep (Welch et al 2009). It is reported that especially the alkaloid, cyclopamine, has toxic effects on the fetus at the day 14 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that especially the alkaloid, cyclopamine, has toxic effects on the fetus at the day 14 of pregnancy. Thus, it causes craniofacial defects and embryonic death that can be seen later (Welch et al 2009, Welch et al 2012. The teratogenic Veratrum alkaloid cyclopamine inhibits sonic hedgehog signal transduction pathway directing the embriyonic cell development and differentiation at the phase of embryonic period (Incardona et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation